We Really Need Clear Guidelines and Recommendations for Safer and Proper Use of Aripiprazole and Risperidone in a Pediatric Population: Real-World Analysis of EudraVigilance Database - Rafaniello, Concetta; Sullo, Maria Giuseppa; Carnovale, Carla; Pozzi, Marco; Stelitano, Barbara; Radice, Sonia; Bernardini, Renato; Rossi, Francesco; Clementi, Emilio; Capuano, Annalisa (Frontiers in Psychiatry, 2020)
Background: Although aripiprazole and risperidone are widespread used in pediatrics, there are still limited evidences on their actual safety profile. By using Eudravigilance database we carried out an analysis to perform a comprehensive overview of reported adverse events among children and adolescents treated with aripiprazole and risperidone. Methods: descriptive analysis was performed of all Individual Case Safety Reports (ICSRs) submitted to EudraVigilance associated to aripiprazole and risperidone and related to paediatric population from 2016 to 2018. Results: A total of 855 and 2,242 ICSRs for aripiprazole and risperidone respectively were recorded, for a total of 11,042 suspected adverse drug reactions (ADRs) (2993 for aripiprazole and 8049 for risperidone). Most of ISCRs were related to male patients (65.0% and 86.3% for aripiprazole and risperidone respectively) and were serious (81.0% and 94.1% for aripiprazole and risperidone respectively). Schizophrenia spectrum and other psychotic disorders, disruptive, impulse-control and conduct disorders and autism spectrum disorder, were the top three clinical indications for aripiprazole (19.0%; 16.1%; 11.6% respectively). For risperidone, ADHD (25.4%), disruptive, impulse-control and conduct disorders (17.1%) and bipolar and related disorders (14.2%) were more commonly reported as clinical indications. Data showed also a high proportion of use for clinical conditions not authorized in children. Psychiatric disorders were the main related adverse events for aripiprazole (20.2%) and among these, suicidal behavior was the one of the most reported (14.9%). Reproductive system and breast disorders were the main related adverse events for risperidone (19.8%) and gynecomastia was the most reported event; metabolism and nutrition disorders, mainly reported as weight gain disorders, were more reported in children (3-11 years) than in adolescents (12-17 years). Conclusions: Our results demonstrate that spontaneously reported adverse events associated to aripiprazole and risperidone reflect what is already known in terms of safety profile, although with about 90% of them being serious. This analysis stress the need of further studies and of effective training and information activities in order to better define the actual benefit/risk ratio of these drugs in paediatric patients.